(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article analyzes the historical experience of the formation of military tactics and strategy in the global context. The essence of such a feature of tactical and special training of police officers in martial law conditions is considered, as the focus on ensuring high combat readiness of personnel through the prism of taking into account readiness for various combat situations that can occur not only on the battlefield, but also suddenly arise in settlements, the author’s recommendations are given on taking into account this feature during tactical training classes in the system of police officer training. Attention is drawn to such features of tactical and special training of police officers in martial law conditions as the need for personnel to acquire skills related to group performance of operational tasks and the focus on acquiring psychophysical readiness to perform the tasks set. It is noted that in the process of forming psychophysical readiness of police officers to perform tasks in martial law conditions, the role of special psychological training is actualized. It is emphasized that in tactical and special training classes it is impossible to fully recreate combat conditions with all the stimuli and factors that influence the actions of personnel in real conditions. However, this is considered possible with the help of virtual reality technologies.